The Influence of Basal Medium on Polyphenol Accumulation in Shoot Cultures of Clerodendrum trichotomum and Clerodendrum colebrookianum - Jan Gomulski; Marta Krzemińska; Magdalena Jochymek; Anna K. Kiss; Izabela Grzegorczyk-Karolak (Molecules)
Plants of the Clerodendrum genus, known for their rich phytochemical profiles, are used in traditional Chinese, Korean, Japanese, and Indian medicine to treat various ailments, including inflammation, hypertension, diabetes, hyperlipidemia, and cancer. Due to the limited natural availability of these plants, there is a growing interest in utilizing in vitro culture techniques to produce their bioactive compounds sustainably. In this study, the effects are compared of Murashige and Skoog (MS), Woody Plant medium (WP), Gamborg B5 (B5), and Schenk and Hildebrandt (SH) basal media on growth, biomass accumulation, and polyphenolic compound production in shoot cultures of Clerodendrum colebrookianum and Clerodendrum trichotomum. The composition of the culture medium significantly influenced the growth and metabolic profiles of both species. C. trichotomum exhibited the highest proliferation potential on WP and SH media, while C. colebrookianum was similar on WP, SH, and B5 media (multiplication factor of about 20). Dry weight accumulation was highest in C. trichotomum grown on SH medium (0.292 g/culture), while C. colebrookianum achieved a comparable biomass on SH and WP media (0.240 g/culture and 0.228 g/culture, respectively). The chemical analysis showed similar secondary metabolite profiles between the two Clerodendrum species with phenylethanoids such as acteoside being the predominant bioactive compounds in hydromethanolic extracts. WP medium was the most favorable for polyphenol accumulation in C. colebrookianum (64.5 mg/g DW), while the SH medium yielded the highest total polyphenol content in C. trichotomum (36.6 mg/g DW). In this study, the importance is underscored of basal medium selection in optimizing the in vitro production of bioactive polyphenolic compounds in Clerodendrum species, providing a foundation for the sustainable and scalable production of these pharmacologically significant metabolites.